Muslim Family Law and Practices: A Practical Guide to the Laws of Marriage and Dissolution of Marriage: Book Review - Fadli Al Ghifari (Presscience, 2026)
This book “Muslim Family Law and Practices: A Practical Guide to the Laws of Marriage and Dissolution of Marriage” by Abdulrahman (2024) offers a comprehensive exploration of its subject by integrating theoretical perspectives with practical insights. It situates the discussion within contemporary academic and social contexts, highlighting key concepts, debates, and developments that shape current understanding. Through a systematic and accessible approach, the author guides readers to grasp both foundational ideas and emerging issues, making the book relevant for scholars, students, and practitioners alike.